2021
DOI: 10.1021/acsanm.0c03261
|View full text |Cite
|
Sign up to set email alerts
|

Ag and Fe3O4 Comodified WO3 – x Nanocomposites for Catalytic Photothermal Degradation of Pharmaceuticals and Personal Care Products

Abstract: Ag/Fe 3 O 4 /WO 3 − x nanocomposite photocatalysts, which consist of surface plasmon nanoparticle Ag, magnetically recoverable Fe 3 O 4 , and coral-like WO 3 − x , are constructed via two-step hydrothermal and photodeposition processes. The significantly strengthened photothermal catalytic-Fenton degradation performance under light irradiation is attributed to the formation of a hierarchical structure, as follows: (i) the unique 3D coral-like defective WO 3 − x nanorods possess the inherent properties of charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…It can also be analyzed from Figure b that the integrated area of Fe­(II) is higher than that of Fe­(III) as compared to its parent form, which indicates the abundance of a large number of Fe­(II) phases (active form required for photo-Fenton-type reactions) as compared to the Fe­(III) phase . Further, deconvolution of O 1s short scan spectra shows mainly three peaks at ∼530.0, ∼531.2, and ∼532.4 eV, which correspond to Fe–O, surface adsorbed oxygen present in the form of CO 2 , and water adsorbed (Figure c) …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…It can also be analyzed from Figure b that the integrated area of Fe­(II) is higher than that of Fe­(III) as compared to its parent form, which indicates the abundance of a large number of Fe­(II) phases (active form required for photo-Fenton-type reactions) as compared to the Fe­(III) phase . Further, deconvolution of O 1s short scan spectra shows mainly three peaks at ∼530.0, ∼531.2, and ∼532.4 eV, which correspond to Fe–O, surface adsorbed oxygen present in the form of CO 2 , and water adsorbed (Figure c) …”
Section: Resultsmentioning
confidence: 89%
“…Further, the analysis of surface bindings corresponding to respective elements was performed by deconvoluting the short scan spectra of two elements, i.e., F 2p and O 1s . It was found that on deconvolution of Fe 2p , six peaks are observed at ∼711.0, ∼713.0, ∼719.3, ∼724.4, ∼726.4, and ∼728.8 eV for Fe 2p 3/2 (II), Fe 2p 3/2 (III), Fe 2p 3/2 (satellite), Fe 2p 1/2 (II), Fe 2p 1/2 (III), and Fe 2p 1/2 (satellite), respectively (Figure b) . It can also be analyzed from Figure b that the integrated area of Fe­(II) is higher than that of Fe­(III) as compared to its parent form, which indicates the abundance of a large number of Fe­(II) phases (active form required for photo-Fenton-type reactions) as compared to the Fe­(III) phase .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations